The impact of agricultura insuranc risk management in achieving the economic development: Applied research in the National Insurance Company (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract                                                                The research aims to investigate the existence of correlations and influence between agricultural insurance risk management and economic development in the National Insurance Company with farmers, as agriculture is one of the leading branches of the national economy, ensuring food security and eliminating poverty to ensure sustainable economic growth through agricultural insurance policies (both the vegetable part (and livestock) and providing agricultural services and guidance to farmers. The research adopted statistical methods, as (30) survey forms were distributed to employees of the researched company, in addition to conducting personal interviews with representatives of the agricultural insurance department. This study relied on the descriptive analytical approach, and highlighted the results it reached. Research: There is a correlation and influence between agricultural insurance risk management and economic development  .